(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Gerbera (Gerbera jamesonii) is an important ornamental plant known for production of cut flowers. In gerbera massive losses occur due to diseases affecting gerbera growth and development. Among all the diseases, fungal diseases have been found to cause enormous losses. There is need for proper management and reduction of fungal pathogens infecting gerbera plant. The causative agents of diseases were isolated and identified by using morphological and molecular charactoristics. Molecular characterization involved isolating DNA from fungal isolate, PCR amplification of ITS region. Invitro antifungal activity of parthenium extract against Alternaria was carried out by using PDA cultures. The biocontrol potential of Parthenium was evaluated against Alternaria. The Parthenium extracts showed significant antifungal activity against isolated strain of fungal pathogens. Experimental result indicated that lower dilution of extracts, the antifungal activity was maximum.